The role of odor receptor protein Or22a in Drosophila melanogaster oviposition and the response spectra of chimeric receptor protein Or22a-b - Pettersson,Lovisa (2018)
The fruit fly Drosophila melanogaster has a well-studied olfactory system. A crucial part of the olfactory system is the olfactory sensory neurons (OSNs). One type of these OSNs, Ab3a, expresses the Odor receptors (ORs) Or22a and Or22b. Or22a is known to play an important role for behaviors like oviposition, but no strong ligand has been found for Or22b. Recent studies have shown that D. melanogaster prefers to oviposit on marula fruit. The volatile in marula fruit that is believed to attract the flies is called ethyl isovalerate. A strain of D. melanogaster that expresses a chimeric olfactory receptor Or22a-b has also recently been found. We wanted to find out if the Ab3a neurons respond to ethyl isovalerate and how the expression of Or22a-b affects the response spectrum of the neuron. We also wanted to find out if Or22a is a key factor for to the preference for oviposition on marula fruit in D. melanogaster. Therefore, we have performed single sensillum recordings (SSR) to find out if D. melanogaster responds to ethyl isovalerate, and if the expression of Or22a-b instead of Or22a and Or22b affects the response spectrum of the Ab3a neurons. To see if Or22a affects the oviposition choice of the flies, we have performed a behavioral assay. We found that the Ab3a neurons in D. melanogaster respond to ethyl isovalerate. The expression of Or22a-b does change the response spectra. The flies that express Or22a-b exhibit lower response to ethyl hexanoate, and higher response to ethyl isovalerate than flies that express Or22a and Or22b in the Ab3a neurons. In conclusion, we have found that the Ab3a neurons in D. melanogaster respond to ethyl isovalerate, and the responsible OR for this response is probably Or22a, since Or22b has no known function. Flies that carry a mutation in the Or22a gene exhibit a different response spectrum than wild type flies. Or22a is an important OR for the finding of oviposition sites.